PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN BERKUNJUNG DI ECO BAMBU - Rani Angraeni, - (2020)
Abstract - This study aims to analyze the effect of personal selling which consists of approach, presentation, handling objective, negotiation, close in purchase decisions at ECO BAMBU. The research method used is an explanatory survey with a cross sectional method approach with a total sample of 72 consisting of PIC (Person in Charge) group consumers who visited ECO BAMBU. Data analysis technique used is path analysis technique. The implementation of personal selling in ECO BAMBU is in the high category and purchase decision is in the high category. Personal Seling which consists of approach, presentation, handling objective, negotiation and close has a positive effect on purchase decisions with the approach sub variable having the highest influence where as an evaluation and input to service quality, product quality to be even better ECO BAMBU. The results showed that there was a significant influence between personal selling on purchase decisions. Keywords - purchase decision, personal selling Keywords: Purchase decision, personal selling and ECO BAMBU